Spain : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper quantifies the macroeconomic effects of fiscal policy in Spain, focusing on the external sector. It describes the stylized facts of the Spanish economy and presents an econometric analysis. It examines Spain's growth and productivity performance in relation to a broad sample of peer economies with an emphasis on recent trends and growth implications. It also employs growth accounting and discusses the productivity lag of Spain.